2012
DOI: 10.1007/s00449-012-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Chitin and L(+)-lactic acid production from crab (Callinectes bellicosus) wastes by fermentation of Lactobacillus sp. B2 using sugar cane molasses as carbon source

Abstract: Crab wastes are employed for simultaneous production of chitin and L(+)-lactic acid by submerged fermentation of Lactobacillus sp. B2 using sugar cane molasses as carbon source. Response surface methodology was applied to design the culture media considering demineralization. Fermentations in stirred tank reactor (2L) using selected conditions produced 88% demineralization and 56% deproteinization with 34% yield of chitin and 19.5 gL(-1) of lactic acid (77% yield). The chitin purified from fermentation display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 20 publications
1
20
1
1
Order By: Relevance
“…Based on crab weight, we obtained 7.5% yield by chemical hydrolysis and 6.9% yield by lactic fermentation. However, these yields were lower as compared to the ones reported in the literature: 20, 30 and 45% [ 10 , 15 , 29 ]. It is important to take into account that total chitin percentage in Allopetrolisthes punctatus is 14.2%, therefore 50% is lost during the purification processes.…”
Section: Resultscontrasting
confidence: 68%
“…Based on crab weight, we obtained 7.5% yield by chemical hydrolysis and 6.9% yield by lactic fermentation. However, these yields were lower as compared to the ones reported in the literature: 20, 30 and 45% [ 10 , 15 , 29 ]. It is important to take into account that total chitin percentage in Allopetrolisthes punctatus is 14.2%, therefore 50% is lost during the purification processes.…”
Section: Resultscontrasting
confidence: 68%
“…Some authors have reported that DP and DM takes altogether between 2 to 7 days (Sorokulova et al 2009;Aytekin & Elibol 2010;Khorrami et al 2012;Zhang et al 2012;Mao et al 2013;Ghorbel-Bellaaj et al 2013;Hajji et al 2015;Sedaghat et al 2015;Francisco et al 2015;Zhang et al 2016;Rawia et al 2016;Sedaghat et al 2017;Chakravarty et al 2018;Doan et al 2019). Some other authors have reported processing time between 24 to 254 hours (Hoffmann et al 2010;Prameela et al 2010;Wahyuntari et al 2011;Pacheco et al 2011;Duan et al 2012;Flores-Albino et al 2012;Mao et al 2013;Junianto et al 2013;Liu et al 2014;Pachapur et al 2015;Mhamdi et al 2017;Aranday-Garcia et al 2017;Neves et al 2017;Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Demineralization ( ria (Castro et al 2018;Chakravarty et al 2018;Aranday-García et al 2017;Neves et al 2017;Zhang et al 2016;Francisco et al 2015;Junianto et al 2013;Zhang et al 2012;Flores-Albino et al 2012;Khorrami et al 2012;Duan et al 2012;Wahyuntari et al 2011;Pacheco et al 2011;Aytekin & Elibol 2010).…”
Section: Deproteinization (Dp)mentioning
confidence: 99%
“…A maximum lactic acid concentration of 35 g/L was obtained. In another study by Flores-Albino et al (2012), it was reported that the maximum lactic acid production was 19.5 g/L using a strain of Lactobacillus sp. B2.…”
Section: Validation Of the Modelmentioning
confidence: 96%